miRNome Profiling of Purified Endoderm and Mesoderm Differentiated from hESCs Reveals Functions of miR-483-3p and miR-1263 for Cell-Fate Decisions - Daichi Ishikawa; Ulf Diekmann; Jan Fiedler; Annette Just; Thomas Thum; Sigurd Lenzen; Ortwin Naujok (Stem Cell Reports, 2017)
Summary: Pluripotent stem cells hold great promise for regenerative medicine since they can differentiate into all somatic cells. MicroRNAs (miRNAs) could be important for the regulation of these cell-fate decisions. Profiling of miRNAs revealed 19 differentially expressed miRNAs in the endoderm and 29 in the mesoderm when analyzing FACS-purified cells derived from human embryonic stem cells. The mesodermal-enriched miR-483-3p was identified as an important regulator for the generation of mesodermal PDGFRA+ paraxial cells. Repression of its target PGAM1 significantly increased the number of PDGFRA+ cells. Furthermore, miR-483-3p, miR-199a-3p, and miR-214-3p might also have functions for the mesodermal progenitors. The endoderm-specific miR-489-3p and miR-1263 accelerated and increased endoderm differentiation upon overexpression. KLF4 was identified as a target of miR-1263. RNAi-mediated downregulation of KLF4 partially mimicked miR-1263 overexpression. Thus, the effects of this miRNA were mediated by facilitating differentiation through destabilization of pluripotency along with other not yet defined targets. : In this article, Ishikawa and colleagues show that miRNAs can regulate early cell-fate decisions during differentiation of human ESCs. miRNome profiling in pure endoderm and mesoderm revealed differentially expressed miRNAs. The endoderm-specific miR-489-3p and miR-1263 increased endoderm specification. The miR-1263 effect was mediated by KLF4 repression. The mesoderm-specific miR-483-3p regulated the generation PDGFRA+ paraxial cells via PGAM1 repression. Keywords: microRNA, miRNome, human pluripotent stem cell, endoderm, mesoderm, cell-fate decision, purified population